The complete mitochondrial genome of Amphinemura claviloba (Wu, 1973) (Plecoptera: Nemouridae) - Chen, Jiajia; Cao, Jinjun; Chen, Mengdan; Chen, Sijin; Li, Weihai; Wang, Ying (Zootaxa, 2020)
We sequenced the complete mitochondrial genome (mitogenome) of a stonefly, Amphinemura claviloba (Wu, 1973), of the family Nemouridae (Insecta: Plecoptera). The mitogenome was 15,707 bp long and contained typical 37 genes with an A+T content of 68.5%. All protein-coding genes (PCGs) use standard initiation codons (methionine and isoleucine), except ND1 and ND5 which starts with TTG and GTG, respectively. Two of the 13 PCGs harbor the incomplete termination codon. All tRNA genes have typical clover secondary structures, except the dihydrouridine (DHU) arm of tRNASer(AGN) forms a simple loop. Secondary structure models of the ribosomal RNA genes of A. claviloba are similar to those proposed for other insects. We also found some structural elements in the control region, such as tandem repeats, poly-C stretch and microsatellite-like elements, etc. Phylogenetic analyses showed the clades for the Nemoura, Amphinemura, and (Mesonemoura + Sphaeronemoura + Indonemoura + Protonemura) are well supported in a polytomy.